(untitled) (Italian Review of Legal History, 2019)
The years from April 1796 to September 1802 constitute for Piedmont a dramatic historical period that sees various regime change in less than a decade: the Savoy government (until December 8th 1798), the Republican Provisional Government (until April 2, 1799), the French receivership (until May 28, 1799), the Austro-Russian military occupation (until June 14, 1800), a government commission flanked by a French extraordinary minister and a legislative council (until 19 April 1801) and finally a General Administrator of the 27th Military Division, which governed Piedmont until its annexation to France (22 September 1802). However, it is the so-called years of the "Bufera" (“the storm”), more precisely the period of the six months from December 1798 to the temporary French retreat beyond the Alps in June 1799, those in which are realized institutional changes and complex political evolutions that will bring the integration of Piedmont into the Napoleonic empire. It is a storm that metaphorically upset the political and social structure of the Kingdom of Sardinia, closing an era and starting a new one, in which men belonging to different social classes began to fight against absolutism and for the affirmation in Piedmont of the ideals of the French Revolution. This essay is focus on the "education plans" (particularly those destinated to primary and secondary school) formulated by the provisional Governments that succeeded each other during the cited institutional changes that involved the Kingdom of Sardinia from December 1798 to the time before the annexation of Piedmont to the Grand Nation. Education in fact, in the ideals and conceptions of the Revolution - and in particular starting from the reflections of Michel Le Peletier De Saint-Fargeau - was identified, even by the "Piedmontese Jacobins" as the essential and necessary element to give life to a new society.